Compensatory Strategies in Facing Communication Breakdown Used by EFL Students in Surakarta - Isya, Mifta Muriska (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research applied descriptive qualitative design. It aims to find out how the EFL students overcome their communication breakdown in delivering message or idea to interlocutor also the reason why they use those compensatory strategies. The knowledge of compensatory strategies supported the speaker or EFL students to achieve effective communication. There are two ways to collect the data in this research: observation then been transcript and interview. This research applied purposive sampling. There are 21 participants who are grouped into seven group then they had to present their assignment in front of the class. That class was a content course which forced student to learn another subject and practicing their speaking skill. According to the data analysis, there are several types of compensatory strategies which is one aspect of the taxonomy of communication strategies that can be used by the students. The most dominant compensatory strategy found in this phenomenon was literal translation from their first language. It was followed by non-linguistic means and code switching as the EFL students preference. They employed compensatory strategies in order that their classmates could catch up what the idea of the presentation is.